Studi Epidemiologi Tuberkulosis Paru (TB) di Indonesia: Temuan Survey Kesehatan Indonesia (SKI) 2023 - Listy Handayani (Jurnal Kendari Kesehatan Masyarakat, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis complex with symptoms of coughing more than 2 weeks and accompanied by other symptoms. TB becomes the leading cause of death in the world due to infectious agents, after three years being replaced by coronavirus disease, the main cause of death in TB HIV co-infection and death related to antimicrobial resistance. This study aims to analyze the epidemiological characteristics of TB in Indonesia. This type of research is descriptive observational to describe the epidemiological characteristics (person and place) of TB in Indonesia. The study was conducted in December 2024 used secondary data collection of Indonesian Health Survey (SKI) 2023. Data were processed and analyzed univariately using the Microsoft Excel computer program. The results showed that the highest prevalence of pulmonary TB according to person characteristics was male, elderly age group, low education, fishermen and farmers, and low economic status. Meanwhile, according to place characteristics, the highest prevalence was those living in urban areas. Thus, it is important for policy makers in TB controlling to pay attention to the epidemiological characteristics of pulmonary TB cases so that the planning and interventions carried out are right on target, effective and efficient